ANALISA KELAYAKAN BISNIS PT. SUCOFINDO UNIT PELAYANAN DONDANG - Suyatin, Sahdiannor LCA. Robin Jonathan (EKONOMIA, 2016)
SAHDIANNOR, 2016. Analyze the feasibility business of PT. SUCOFINDO service unit Dondang, under the guidance of Mr. LCA. Robin Jonathan and Mrs. Suyatin.This porpuse of the research is to determine the feasibility business of PT. SUCOFINDO service unit Dondang in term of financial aspects of investment assessment criteria based on PP, NPV, IRR, ARR, PI.Based on the five aspect can be shown that the investment for the coal laboratory in PT. SUCOFINDO service unit Dondang acceptable and feasible to run. The calculation of the five methods of business feasibility analisysis tool by calculation as follows : payback period method showed that the time required to cover the investment of RP 12,841,491,000.- is 2 years 8 months 5 days faster of economic life of the laboratory instrument which is 4 years. ARR (Average Rate of Return) methods showed that the average rate of profit is 86.49%. NPV Methods can be Â a positive value is Rp 12,877,069,440.-. from IRR (internal Rate Return) methods obtained interest rate is 36.9%. this result showed that the rate of return greather than the interest rate determined is 6%. While PI (Profitability Index) methods result showed greather than 1 which is 2.00.The calculation of the five methods can be decided that the investment coal laboratory in PT. SUCOFINDO service unit Dondang acceptable and feasible to run.